PERBANDINGAN HASIL BELAJAR KIMIA MENGGUNAKAN MODEL PEMBELAJARAN NHT DAN TPS PADA MATERI ELEKTROLIT DAN NON ELEKTROLIT - Esse Khoirunnisa; Hartatiana Hartatiana; Pandu J Laksono (Chemistry Education Department of Education and Teaching Faculty, 2019)
The purpose of research is(1)to find out the chemistry learning outcomes taught using the Numbered Head Together learning model (2) knowing the chemistry learning outcomes taught using Think Pair Share learning model (3) knowing the differences in chemistry learning outcomes of students taught using the NHT model and chemistry learning outcomes taught using TPS model. This research is a quasy eksperimental with Pra-Post Test Control Group Design. Population in this study is class X IPA1-5 amounting to 180. The sampling technique was purposive sampling in class X IPA 2 and X IPA 4. Data collection techniques using observation, documentation and test questions pra-post test. Data analysis techniques are descriptive statistics, inferential statistics and analysis prerequisite tests. The results were obtained in both classes through descriptive statistical analysis namely the average learning outcomes using the numbered head together model = 72,50 while the average learning outcomes using the model Think Pair Share = 69,17. Results of inferential statistical data obtained tcount 3,508> ttable 2,004. It can be concluded that H0 is rejected which means that there are differences in Numbered Head Together learning model with Think PairShare learning model on student learning outcomes in class X IPA SMA 22 Palembang on electrolyte and non-electrolyte material. It can be concluded that H0 is rejected, which means that there is a difference between the NHT model and the TPS model towards student learning outcomes on electrolyte and non-electrolyte material in class X IPA senior high school in Palembang.